2016
DOI: 10.1002/ange.201607397
|View full text |Cite
|
Sign up to set email alerts
|

Benign‐by‐Design Solventless Mechanochemical Synthesis of Three‐, Two‐, and One‐Dimensional Hybrid Perovskites

Abstract: Organic–inorganic hybrid perovskites have attracted significant attention owing to their extraordinary optoelectronic properties with applications in the fields of solar energy, lighting, photodetectors, and lasers. The rational design of these hybrid materials is a key factor in the optimization of their performance in perovskite‐based devices. Herein, a mechanochemical approach is proposed as a highly efficient, simple, and reproducible method for the preparation of four types of hybrid perovskites, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…[20][21][22] It is therefore important to develop alternative greener approaches with scale-up capability such as mechanochemical synthesis, also known as ball milling, that avoids or minimizes the use of organic solvents. [23][24][25][26][27] A few reports have covered the mechanochemical synthesis of organicinorganic halide perovskites, [23][24][25] double halide perovskites, 26 and CsPbBr 3 quantum dots. 27 Further progress is still needed on the mechanochemical synthesis of all-inorganic halide perovskite nanocrystals such as CsPbBr 3 with control over size and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] It is therefore important to develop alternative greener approaches with scale-up capability such as mechanochemical synthesis, also known as ball milling, that avoids or minimizes the use of organic solvents. [23][24][25][26][27] A few reports have covered the mechanochemical synthesis of organicinorganic halide perovskites, [23][24][25] double halide perovskites, 26 and CsPbBr 3 quantum dots. 27 Further progress is still needed on the mechanochemical synthesis of all-inorganic halide perovskite nanocrystals such as CsPbBr 3 with control over size and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The enlarged parts represent the corresponding TEM images of CH 3 NH 3 PbBr 3 nanocrystals. (f) Scheme of the mechanochemical synthesis for the 3D, 2D and 1D perovskites [54].…”
Section: Other Synthesis Methodsmentioning
confidence: 99%
“…Jodlowski et al reported the preparation of a bi-dimensional (i.e. 2D) perovskite (Gua 2 PbI 4 ) using a mechanochemical synthesis approach (Figure 3f) [54]. The precursors of PbI 2 and MAI were mixed in a 1:1 molar ratio inside a ball mill under ambient conditions to produce polycrystalline powders.…”
Section: Two-dimensional Materials For Photodetectormentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanochemistry has proven to present a simple, reliable and effective route to achieve nanostructured materials and evolved into a highly popular synthesis method in various fields. Consequently, recently a series of review articles on the subject has been published [11–16] and its advantages in enantioselective synthesis [17] , 17 O labelling [18] , ettringite synthesis [19] , MOF preparation [20] , pharmaceutical synthesis [21] and hybrid perovskites [22] were demonstrated. Other works highlighted that increased product selectivity is achievable [23] or focused more on the mechanochemical process itself [24,25] .…”
Section: Introductionmentioning
confidence: 99%